Interpretation of Historical Images in Khayriddin Sultan's Stories - G.A.Yunusaliyeva (Genius Publishing Group, 2022)
In the article, the historical images in Khayriddin Sultan's stories, their interpretationand the mentality of the characters in the work were analyzed
Keywords: Character, episode, artistic expression, poetic essence, image, episode.